2009
DOI: 10.1016/j.healthplace.2008.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Does where you live influence what you know? Community effects on health knowledge in Ghana

Abstract: This paper examines community effects on health knowledge in a developing country setting. We examine knowledge about the etiology and prevention of child illnesses using a unique 2002 representative survey of communities and households in Ghana. We find that community context matters appreciably, even after adjusting for the anticipated positive effects of an individual's education, literacy, media exposure and household socioeconomic status. The proportion of literate adults and the presence of a market in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…However, poorly communicated health messages may not only result in inaccurate knowledge, but can also be potentially harmful as such misinformation can lead to poor health-seeking practices. The chronic lack of effective health information, communication and education systems as evident from the findings is especially relevant structural condition and policy failure in the context of UWR, where a legacy of low educational attainment means that a large section of the population does not possess a high enough level of health literacy to accurately discern the contents of HBV messages, or be connected to social networks that properly understand and can pass on the correct information (Andrzejewski et al, 2009). In the absence of correct preventive health information, the underlying sociocultural belief system will tend to provide the basis for conceptualizing health issues related to an unknown disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, poorly communicated health messages may not only result in inaccurate knowledge, but can also be potentially harmful as such misinformation can lead to poor health-seeking practices. The chronic lack of effective health information, communication and education systems as evident from the findings is especially relevant structural condition and policy failure in the context of UWR, where a legacy of low educational attainment means that a large section of the population does not possess a high enough level of health literacy to accurately discern the contents of HBV messages, or be connected to social networks that properly understand and can pass on the correct information (Andrzejewski et al, 2009). In the absence of correct preventive health information, the underlying sociocultural belief system will tend to provide the basis for conceptualizing health issues related to an unknown disease.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that research needs to take into account social support that people can draw on when problems arise due to their health literacy limitations. Other researchers suggested that social networks and diffusion [14,15] played a key role in health knowledge, and social capital [16] dimensions also covariate with health literacy. And it is argued that social capital is a key factor of health literacy.…”
Section: Introductionmentioning
confidence: 99%
“…It is documented that knowledge and discussions about vaccination improve uptake [12]. The relative proportion of literate adults in local communities may also have a general positive effect on the presence of health knowledge in local communities [13]. Literacy not only improves the situation for those that have an education, but might also have an effect on the uptake of vaccines for those that are not literate but live in regions with a relatively high proportion of literacy.…”
Section: Introductionmentioning
confidence: 99%